Insights into ecological role of a new deltaproteobacterial order Candidatus Acidulodesulfobacterales by metagenomics and metatranscriptomics - Tan, Sha; Liu, Jun; Fang, Yun; Hedlund, Brian P.; Lian, Zheng-Han; Huang, Li-Ying; Li, Jin-Tian; Huang, Li-Nan; Li, Wen-Jun; Jiang, Hong-Chen; Dong, Hai-Liang; Shu, Wen-Sheng (The ISME Journal, 2019)
Several abundant but yet uncultivated bacterial groups exist in extreme iron- and sulfur-rich environments, and the physiology, biodiversity, and ecological roles of these bacteria remain a mystery. Here we retrieved four metagenome-assembled genomes (MAGs) from an artificial acid mine drainage (AMD) system, and propose they belong to a new deltaproteobacterial order, Candidatus Acidulodesulfobacterales. The distribution pattern of Ca . Acidulodesulfobacterales in AMDs across Southeast China correlated strongly with ferrous iron. Reconstructed metabolic pathways and gene expression profiles showed that they were likely facultatively anaerobic autotrophs capable of nitrogen fixation. In addition to dissimilatory sulfate reduction, encoded by dsrAB , dsrD , dsrL , and dsrEFH genes, these microorganisms might also oxidize sulfide, depending on oxygen concentration and/or oxidation reduction potential. Several genes with homology to those involved in iron metabolism were also identified, suggesting their potential role in iron cycling. In addition, the expression of abundant resistance genes revealed the mechanisms of adaptation and response to the extreme environmental stresses endured by these organisms in the AMD environment. These findings shed light on the distribution, diversity, and potential ecological role of the new order Ca . Acidulodesulfobacterales in nature.